Si decline and diatom evolution: Insights from physiological experiments - Petrucciani, Alessandra; Knoll, Andrew H.; Norici, Alessandra (Frontiers in Marine Science, 2022)
In today’s oceans, diatoms are abundant and diverse primary producers distinguished by their silica shells. Although molecular clocks suggest that diatoms arose as much as 250 million years ago (Ma), the earliest known diatom fossils date from 190 Ma, leading to the suggestion that early diatoms were at best lightly silicified. By the Cretaceous Period, large circular (in cross section) diatoms with highly silicified frustules thrived in surface oceans, only later to be joined by species with elongated and thinner frustules, as well as lower SiO2 content. Decreased Si availability in surface oceans has been proposed as a principal driver of diatom evolution. Here, we investigate this through physiological experiments assessing the functional acclimation response of diatoms to reconstructed paleo-seawater. Four diatom species, differing in size and shape, were acclimated to reconstructed paleoenvironments mimicking Mesozoic/Cenozoic concentrations of nutrients in the presence of different Si regimes. When exposed to 500 µM Si, all populations, save for that of Conticribra weissflogii, became more highly silicified; the higher Si content per cell at 500 µM Si coincided with slower growth in small-sized cells. All species except C. weissflogii also showed lower photosynthetic efficiency as well as greater cell volume in comparison with diatoms acclimated to 205 or 25 µM Si. Average cell stoichiometry correlates with cell shape, but not size; pennates, in particular Phaeodactylum tricornutum, showed an acclimatory response to Si regimes, modulating Si use efficiency (the lower the external Si concentrations, the higher the C and N quotas per Si). Experimental data suggest that in the densely silicified and bigger C. weissflogii grown at higher Si, diffusion of silicic acid across membranes made a larger contribution to Si uptake, saving energy which could be reallocated into growth. In contrast, for less highly silicified and smaller species, high energy costs of Si homeostasis needed to prevent the overaccumulation of intracellular Si limited growth. While our experimental species reacted individualistically to changing silica availability, with distinct levels of plasticity, selective pressure associated with the temporal decline in Si availability may well have favored elongated shapes. Modern, less silicified species are unable to exploit high Si concentrations.